Mouse models for enteral and parenteral nutrition after surgery - Kong, Can; Kong, Dingsheng; Hu, Junjie; Liao, Lianggong; Xiong, Zhiguo; Fu, Tao (Frontiers in Veterinary Science, 2025)
BackgroundThis study aims to establish a mouse model with different nutritional support modalities [enteral nutrition (EN) and parenteral nutrition] after abdominal surgery, providing a stable and effective animal model for further study on the intestinal barrier damage caused by total parenteral nutrition.MethodsTwenty mice were randomly assigned to either an enteral nutrition (EN) group (n = 10) or a total parenteral nutrition (TPN) group (n = 10). After abdominal surgery via appendectomy, the two groups of mice received different modes of nutritional support (TPN or EN). A properly sized central venous catheter was placed in the right internal jugular or an enteral nutrition catheter was inserted into the duodenum. Parenteral or enteral nutrition was infused through these catheters. The survival rate, intestinal villus height, epithelial cell proliferation, changes in goblet cells and Paneth cells, as well as the expression levels of the tight junction (TJ) proteins ZO-1 and occludin, were observed.ResultsNo difference was found in survival rate (P < 0.01) between the two groups. However, significant differences were observed in the height of small intestinal villi, epithelial proliferation rate, number of goblet cells [Periodic Acid-Schiff (PAS+)], Paneth cell function (Lysozyme+), and expression of ZO-1 and occludin proteins. All of these markers were significantly decreased in the TPN group compared to the EN group (P < 0.05).ConclusionThe mouse model is suitable and effective for investigating the pathogenesis of intestinal barrier dysfunction, as it provides different types of nutritional support after abdominal surgery.